Validity and reliability tests on generalized anxiety disorder diagnostic scale - Valensia Putri Adhyartasari; Christiana Hari Soetjiningsih; Susana Prapunoto (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Generalized anxiety disorder is one of the most common anxiety disorders in society. The purpose of this study is to develop a diagnostic scale for generalized anxiety disorder because there is no self-report diagnostic tool for generalized anxiety disorder based on DSM-V and ICD-10 criteria in Indonesia. The research uses quantitative research. Respondents in the field test consisted of 210 adult respondents aged 18-65 years, moderate or had experienced anxiety, and were Indonesian citizens. This study provides the results that the overall anxiety disorder diagnostic scale has gone through the internal validity and internal reliability test stages and obtained valid and reliable results so that this measuring instrument has described the suitability of the measuring instrument construct with the data. Based on testing the average processing time of 6 respondents, it was obtained an average of approximately 5 minutes (2 minutes 4 seconds to 5 minutes 21 seconds). Scoring for each item that supports or is in accordance with the symptoms (favorable), namely Yes = 1 and No = 0. The scoring for each item that does not support the symptoms is Yes = 0 and No = 1. This measuring instrument is declared to have good validity and reliability.